Definitions of Hemodynamic Instability Related to Renal Replacement Therapy in Critically Ill Patients: A Systematic Review Protocol - Jean Zhuo Wang; Lindsey Sikora; Peter Farrell; Swapnil Hiremath; Edward G. Clark (Canadian Journal of Kidney Health and Disease)
Background: Hemodynamic instability related to renal replacement therapy (HIRRT) is a common complication affecting critically ill patients that require renal replacement therapy (RRT). There is currently no consensus regarding the definition of HIRRT in critically ill patients. In this context, the impacts of HIRRT on clinical outcomes such as mortality or renal recovery in critically ill patients are unclear. Objective: The primary objective of this proposed systematic review is to evaluate the association between HIRRT and clinical outcomes, as reported within randomized control trials in the literature. The secondary objective of this systematic review is to compare rates of HIRRT, according to various definitions used by randomized controlled trials, across different RRT modalities used to treat critically ill patients, with the goal of paving the way toward a common definition of HIRRT for future research. Design: Systematic review and meta-analysis Measurements: The rates of HIRRT, mortality, and renal recovery will be reported according to each definition of HIRRT Patients: Critically-ill adults with acute kidney injury admitted to intensive care units Methods: The search strategy will be developed to identify articles in Medline, MEDLINE In-Process, EMBASE, and Cochrane CENTRAL Registry. We will include randomized control trials examining renal replacement therapy in critically ill patients. This will include intermittent hemodialysis (iHD), all forms of prolonged intermittent RRT (PIRRT), and continuous renal replacement therapy (CRRT). Only articles that report a definition of HIRRT and the rates of HIRRT will be included in our analysis. Two reviewers will independently screen all articles for inclusion and exclusion. Data extraction and quality assessment will be also performed in duplicate. All disagreements will be resolved through discussion or a third reviewer. Limitations: The heterogeneity in the definitions of HIRRT and outcome reporting may limit the ability to perform meta-analysis and perform comparisons in the rates of HIRRT between RRT modalities. Conclusions: This systematic review aims to assess the association between HIRRT and important clinical outcomes. In doing so, we will identify definitions of HIRRT within the current literature and the rates of HIRRT associated with these definitions. HIRRT can result in early discontinuation of dialysis, organ injury from hypoperfusion, and may negatively impact mortality and renal recovery in critically ill patients. This systematic review will synthesize the impact and frequency of HIRRT reported in the literature and, in doing so, may help determine the extent to which common definitions of HIRRT might be recommended for standardized use in future research related to HIRRT. Systematic Review Registration: PROSPERO registration number: CRD42023396550.